2019
DOI: 10.1080/02670836.2019.1570679
|View full text |Cite
|
Sign up to set email alerts
|

Solute segregation effect on grain boundary migration and Hall–Petch relationship in CrMnFeCoNi high-entropy alloy

Abstract: Homogenisation has been used to eliminate solute segregation of CrMnFeCoNi high-entropy alloys (HEAs) before thermomechanical processing. To overcome the deficiencies caused by high-temperature homogenisation, we cancelled the homogenisation and studied the solute segregation feature and its effect on the grain growth and the mechanical property. The HEA forms equiaxed grains with the solute segregation in the range of tens of micrometres after cold rolling and recrystallisation. The grain growth in recrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…Earlier, Liu et al [24] demonstrated a Hall-Petch relationship between the Vickers hardness and the grain size for equiatomic CoCrFeMnNi at 293 K and obtained a k value of 677 MPa•µm −1/2 , which is higher than the values obtained by Liu et al [20] of 394 MPa•µm −1/2 , Otto et al [18] of 494 MPa•µm −1/2 and Sun et al [19] of 586 MPa•µm −1/2 . The higher value may reflect that the Vickers hardness represents the flow stress at 8-10% strain rather than σ y .…”
Section: T (K)mentioning
confidence: 77%
See 3 more Smart Citations
“…Earlier, Liu et al [24] demonstrated a Hall-Petch relationship between the Vickers hardness and the grain size for equiatomic CoCrFeMnNi at 293 K and obtained a k value of 677 MPa•µm −1/2 , which is higher than the values obtained by Liu et al [20] of 394 MPa•µm −1/2 , Otto et al [18] of 494 MPa•µm −1/2 and Sun et al [19] of 586 MPa•µm −1/2 . The higher value may reflect that the Vickers hardness represents the flow stress at 8-10% strain rather than σ y .…”
Section: T (K)mentioning
confidence: 77%
“…Recently, Liu et al [20] determined the Hall-Petch behavior of equiatomic single-phase f.c.c. CoCrFeMnNi at room temperature only.…”
Section: Carbon Doping-cocrfemnnimentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the relationship between porosity and strength of porous materials can be simulated by the Barsen equation [17]. The Hall-Petch equation can be used to reveal the relation between the strength or hardness and the grain size of single phase material [18][19][20] or composite material [21][22][23]. In this work, a series of porous Ti 3 SiC 2 compounds with different pore sizes and approximately the same porosities and phase purities were prepared by the reactive synthesis of elemental powders through a pressure less sintering process.…”
Section: Introductionmentioning
confidence: 99%